Species diversity, above and below ground living biomass, and carbon stock assessments og mangroves in station 1, Tandog iIsland, Taklong Island National Marine Reserve, Nueva Valencia, Guimaras - Nonod, Alain Jeff (2018.)
The role and services that mangrove forests provide are now widely recognized but it is only recently that their role in climate change mitigation has been given serious consideration. Mangroves sequester and store carbon that could be as three times of what tropical forests can store. Tandog Island is inside Taklong Island National Marine Reserve which is a marine protected area with an extensive mangrove cover. Studies on carbon stock determination in the country mostly focused on disturbed forests and there have been limited studies done to assess the amount of carbon stored in protected areas thus this study provides an important baseline data for comparison with other mangrove forests in the country. This study aimed to determined the diversity of mangroves and quantify the amount of above and belowground biomass and carbon stored in Station 1 in Tandog Island. Specifically, this study aimed to (1) determine the area and map out the selected mangrove patches, (2) assess the species composition and community structure, (3) determine above and belowground biomass and carbon stock of live vegetation, and (4) convert the total carbon density into their carbon dioxide equivalents. Published allometric equations were utilized in the study and measurements were only limited in vegetation. The surveyed mangroves in Tandog Island contained 14 species coming from 8 plant families. The stand basal area of 19.43 m2/ha is indicative of a mature community system and shows how the area being protected benefited its status. Further, a high tree density and wildling density were also observed which translate into high regeneration capacity of the community. The average biomass obtained was 142.66 Mg/ha which is equivalent to 66.47 Mg/ha C and 243.95 Mg/ha CO2e. The estimated total biomass for the surveyed site based on total mangrove area of 5.32 hectares was 758.61 Mg and the total carbon stored was 353.63 Mg C which is equivalent to 1297.82 Mg of carbon dioxide emission potential. These values reflect the capacity of the protected mangrove forests in Tandog Island as carbon sinks through sequestrating and storing high amounts of atmospheric carbon to mitigate the impacts of climate change at the local level which contributes to the global initiatives in countering climate change progression.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Mangroves -- Taklong Island National Marine Reserve -- Nueva Valencia, Guimaras